Al-doping effect on the surface morphology of zno films grown by reactive rf magnetron sputtering - Silva, Erica Pereira da; Chaves, Michel; Silva Junior, Gilvan da; Baldo de Arruda, Larissa; Lisboa-filho, Paulo Noronha; Durrant, Steven Frederick; Bortoleto, José Roberto Ribeiro [UNESP] (Scientific Research Publishing, 2013)
Zinc oxide (ZnO) and aluminum-doped zinc oxide (ZnO:Al) thin films were deposited onto glass and silicon substrates by RF magnetron sputtering using a zinc-aluminum target. Both films were deposited at a growth rate of 12.5 nm/min to a thickness of around 750 nm. In the visible region, the films exhibit optical transmittances which are greater than 80%. The optical energy gap of ZnO films increased from 3.28 eV to 3.36 eV upon doping with Al. This increase is related to the increase in carrier density from 5.9 × 1018 cm−3 to 2.6 × 1019 cm−3 . The RMS surface roughness of ZnO films grown on glass increased from 14 to 28 nm even with only 0.9% at Al content. XRD analysis revealed that the ZnO films are polycrystalline with preferential growth parallel to the (002) plane, which corresponds to the wurtzite structure of ZnO.
Keywords: ZnO Thin Films; Surface Morphology; RF Magnetron Sputtering